Schoology, Changing A Negative Thinking Pattern About Use of Social Media - Rosy, Brillian (Universitas Sebelas Maret, 2018)
Social media makes the user addicted, it seems to be a negative mindset when reviewing social media. The development of the era brings the development of technology and information, it has a considerable impact on behavior patterns and human thinking. At this time, children or teenagers to adulthood have a strong dependence on information. The need for technology and information is very varied, one easy way to access information is with social media. The use of social media without parental controls in children or adolescents, will have a negative impact. On the other hand also positively influence if its use becomes innovation in the learning process. There are several social media that are used as interactive learning media, now known as Learning Management System (LMS). LMS allows educators to create virtual classrooms as a means of interacting and accessing subject matter anytime and anywhere as long as there is an internet network. One of the social media (LMS) that can be used for learning is Schoology. This research is just a theory study which concludes that e-learning based learning media that is Schoology able to change the negative thinking that has been spread in the community will the use of social media.